BERBAGI PENGETAHUAN SEBAGAI ALTERNATIF PENCIPTAAN PENGETAHUAN UNTUK STAF PENGAJAR VOKASI UI - Dyah Safitri (Jurnal Vokasi Indonesia, 2013)
ABSTRACT -The process of knowledge sharing becomes important processes for an organization in creatingnew knowledge and innovation. Tacit and explicit knowledge can be moved through several processes toknowledge sharing. Culture an important part of the process, especially an appreciation of the sources ofknowledge that is willing to share the knowledge. In educational organizations especially recently establishedsuch as Vocational Program UI should institutionalization of knowledge as a knowledge center will bebeneficial in the process of knowledge sharing.Keywords: Knowledge, Knowledge Sharing, Tacit Knowledge, Explicit Knowledge, KnowledgeTransfer, Knowledge Manager, Knowledge Center